Participation of households in local economic development programme and poverty reduction: Empirical evidence from support to local economy in Mwanza (slem) - Marco, Salu (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the Degree of Master of Science in Economics of Mzumbe University